1991
DOI: 10.1111/j.1600-0773.1991.tb01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lead Poisoning Treated with Dimercaptosuccinic Acid

Abstract: A 54-year-old male with chronic lead poisoning was treated with 2.3-dimercaptosuccinic acid (DMSA). A daily dosage of 30 mg/kg body weight for three days and 20 mg/kg for four days resulted in a decrease of the blood-lead concentration (B-Pb) from 3.7 to 0.7 mumol/l; the total amount of lead excreted in the urine during the first seven 24 hr periods was 75 mumol. After the treatment, B-Pb slowly increased to 3.3 mumol/l. A second treatment was then initiated and resulted in similar changes in B-Pb. However, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 13 publications
1
14
0
3
Order By: Relevance
“…The non-specificity of metal chelating agents and their adverse side effects, including depletion of endogenous essential elements, emphasize the need for an alter- nate to chelation therapy in metal intoxication [8,10,11]. The recent surge for nutritional modulation for prevention or amelioration of chemical toxicity supports this requirement and offers promise [19].…”
Section: Discussionmentioning
confidence: 99%
“…The non-specificity of metal chelating agents and their adverse side effects, including depletion of endogenous essential elements, emphasize the need for an alter- nate to chelation therapy in metal intoxication [8,10,11]. The recent surge for nutritional modulation for prevention or amelioration of chemical toxicity supports this requirement and offers promise [19].…”
Section: Discussionmentioning
confidence: 99%
“…They include gastrointestinal discomfort, skin reaction, mild neutropenia, and elevated liver enzymes. A strong musculocutaneous reaction was reported in one case of chronic lead poisoning (Grandjean et al, 1991) and hemolytic anemia was reported in a worker with occupational lead exposure (Gerr et al, 1994).…”
Section: Meso-23-dimercaptosuccinic Acidmentioning
confidence: 98%
“…31 Outros dois trabalhos, relatando resultados de séries de casos de adultos tratados, mostraram boas eficácia e segurança no uso do DMSA em adultos e crianças. 32,33 Um ensaio clínico com 21 crianças com plumbemias variando entre 31 e 49 mcg/dL (todas com teste de mobilização de chumbo com dose padrão de EDTACaNa 2 positivo), e usando três subgrupos de doses diferentes contra grupo controle com tratamento tradicional com versenato de cálcio, mostrou uma redução significativa de chumbo no sangue durante o ciclo de tratamento, bem como o aumento da excreção urinária de chumbo e retorno dos níveis de ALA-U e ALA-D. O grupo utilizando DMSA não mostrou depleção de metais essenciais como zinco, magnésio, cobre, ferro e cálcio, ao contrário do grupo tratado com versenato. 34 Os níveis de plumbúria de 24 horas no grupo usando DMSA foram comparáveis aos do grupo usando EDTACaNa 2 (Figura 1).…”
Section: Quadrounclassified